background image

n

N

:

totBound

β

(

f

n

)

n

N

:

totBound

α

(

f

0

f

n

)

n

N

:

totBound

β

(

f

0

f

n

)

totBound

α

(

f

0

f

1

f

2

)

totBound

β

(

f

0

f

1

f

2

)

Some of the above defined predicates are equivalent:

Proposition 23.

E

GR

f

n

N

:

thick

α

(

E

n

)

⇔ ∃

n

N

:

totBound

α

(

f

n

)

.

E

GR

f

n

N

:

thick

β

(

E

n

)

⇔ ∃

n

N

:

totBound

β

(

f

n

)

.

Proof.

Because every

F

GR

f

n

is a superset of

E

n

for some

E

GR

f

.

Proposition 24.

E

GR

f

n

N

:

thick

α

(

E

0

E

n

)

⇔ ∃

n

N

:

totBound

α

(

f

0

f

n

)

.

E

GR

f

n

N

:

thick

β

(

E

0

E

n

)

⇔ ∃

n

N

:

totBound

β

(

f

0

f

n

)

.

Proof.

f

0

f

n

=

f

0

f

n

. Thus every

F

GR

(

f

0

f

n

)

we have

F

f

k

, thus

F

E

k

k

for all

k

for some

E

k

GR

f

and so

F

E

0

E

n

where

E

=

E

0

E

k

GR

f

.

Proposition 25.

All predicates in the above list are pairwise equivalent in the case if

f

is a

uniform space.

Proof.

Because

f

f

=

f

.

5